Genetic characteristics, antimicrobial resistance, and prevalence of Arcobacter spp. isolated from various sources in Shenzhen, China - Ma, Yanping; Ju, Changyan; Zhou, Guilan; Yu, Muhua; Chen, Hui; He, Jiaoming; Zhang, Maojun; Duan, Yongxiang (Frontiers in Microbiology, 2022)
Arcobacter spp. is a globally emerging zoonotic and foodborne pathogen. However, little is known about its prevalence and antimicrobial resistance in China. To investigate the prevalence of Arcobacter spp. isolated from various sources, 396 samples were collected from human feces, chicken cecum, and food specimens including chicken meat, beef, pork, lettuce, and seafood. Arcobacter spp. was isolated by the membrane filtration method. For 92 strains, the agar dilution method and next-generation sequencing were used to investigate their antimicrobial resistance and to obtain whole genome data, respectively. The virulence factor database (VFDB) was queried to identify virulence genes. ResFinder and the Comprehensive Antibiotic Resistance Database (CARD) were used to predict resistance genes. A phylogenetic tree was constructed using the maximum likelihood (ML) method with core single-nucleotide polymorphisms (SNPs). We found that 27.5% of the samples (n = 109) were positive for Arcobacter spp., comprising Arcobacter butzleri (53.0%), Arcobacter cryaerophilus (39.6%), and Arcobacter skirrowii (7.4%). Chicken meat had the highest prevalence (81.2%), followed by seafood (51.9%), pork (43.3%), beef (36.7%), lettuce (35.5%), chicken cecum (8%), and human fecal samples (0%, 0/159). Antimicrobial susceptibility tests revealed that 51 A. butzleri and 40 A. cryaerophilus strains were resistant to streptomycin (98.1, 70%), clindamycin (94.1, 90%), tetracycline (64.7, 52.5%), azithromycin (43.1%, 15%), nalidixic acid (33.4, 35%), and ciprofloxacin (31.3, 35%) but were susceptible to erythromycin, gentamicin, chloramphenicol, telithromycin, and clindamycin (≤10%). A. skirrowii was sensitive to all experimental antibiotics. The virulence factors tlyA, mviN, cj1349, ciaB, and pldA were carried by all Arcobacter spp. strains at 100%, and the following percentages were cadF (95.7%), iroE (23.9%), hecB (2.2%), hecA, and irgA (1.1%). Only one A. butzleri strain (F061-2G) carried a macrolide resistance gene (ereA). One A. butzleri and one A. cryaerophilus harbored resistance island gene clusters, which were isolated from pork and chicken. Phylogenetic tree analysis revealed that A. butzleri, A. cryaerophilus, and A. skirrowii were separated from each other. To our knowledge, this is the first report of the isolation of Arcobacter spp. from vegetables and seafood in China. The resistance island gene cluster found in pork and chicken meat and the presence of virulence factors could be a potential risk to human health.